A Study on the Incidence and Predictors of Complications after Open Haemorrhoidectomy - Shah, Rehman; Khan, Abdullah; Nisar, Saliha (Indus Journal of Bioscience Research, 2025)
Background: Open haemorrhoidectomy remains the standard surgical treatment for high-grade haemorrhoids. Despite its efficacy, the procedure is associated with a range of postoperative complications, and understanding their incidence and predictors is essential for improving patient care. Objective: To determine the incidence and predictors of complications following open haemorrhoidectomy. Methods: This cross-sectional study was conducted at Aga Khan Hospital Gilgit from November 2024 to April 2025. A total of 225 patients undergoing open haemorrhoidectomy were included through non-probability consecutive sampling. Demographic, clinical, and intraoperative data were collected, including age, BMI, haemorrhoid grade, comorbidities, duration of surgery, and bleeding volume. Postoperative complications such as pain, bleeding, urinary retention, wound infection, delayed healing, anal stenosis, and recurrence were recorded. Data were analyzed using SPSS version 26, with chi-square tests and multivariate logistic regression applied. Results: Postoperative complications occurred in 37.7% of patients. The most common complications were prolonged pain (24.4%), urinary retention (12.4%), and secondary bleeding (9.3%). Significant predictors of complications included age over 50 years (OR 2.6, p = 0.001), BMI ≥ 30 kg/m² (OR 2.4, p = 0.004), diabetes mellitus (OR 3.1, p < 0.001), smoking (OR 2.2, p = 0.008), intraoperative bleeding over 50 ml (OR 2.5, p = 0.005), and operative duration over 45 minutes (OR 2.1, p = 0.01). Conclusion: It is concluded that open haemorrhoidectomy is associated with a substantial risk of complications, particularly in older, obese, diabetic, and smoking patients, as well as those undergoing longer or more complex surgeries. Preoperative risk assessment and individualized management strategies are recommended to minimize postoperative morbidity.